2019
DOI: 10.1177/0361198119837505
|View full text |Cite
|
Sign up to set email alerts
|

Platoon Priority Visualization Modeling and Optimization for Signal Coordination in the Connected Vehicle Environment

Abstract: Although connected vehicle (CV)-based signal coordination has some proposed prototypes and has been investigated by several different strategies, the existing works have issues that require attention, including additional CV-based system uncertainties and platoon priority request considerations. Thus, a generalized framework consisting of a platoon-based bicyclic coordination diagram (Bi-PCD), a new probabilistic surrogate quantification, and a platoon priority-based offset optimization in the CV environment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In contrast with previous studies that only used loop detector or probe data, Beak et al ( 29 ) compared the progression quality of a CV-based signal system under different strategies, namely free and coordinated operations. Li et al ( 30 ) demonstrated the use of progression quality for optimizing platoon priority-based offset optimization in a CV environment. Day et al ( 31 ) also examined the feasibility of offset optimization using CV data at different penetration rates based on travel time reliability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast with previous studies that only used loop detector or probe data, Beak et al ( 29 ) compared the progression quality of a CV-based signal system under different strategies, namely free and coordinated operations. Li et al ( 30 ) demonstrated the use of progression quality for optimizing platoon priority-based offset optimization in a CV environment. Day et al ( 31 ) also examined the feasibility of offset optimization using CV data at different penetration rates based on travel time reliability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, arrival profiles created by virtual detections were used to obtain signal offset optimization for signal coordination. Furthermore, Beak et al in 2018 [25] proposed a modified Purdue coordination diagram (PCD) utilizing CV data, labelled as CV-PCD, in order to quantitatively evaluate the smooth progression along a corridor [8]. Li et al in 2019 [8] presented an extended offset optimization that targets platoon priority with better signal coordination in a CV environment.…”
Section: Cv-based Signal Coordinationmentioning
confidence: 99%
“…As shown in Figure 6, a signalized intersection located at 109 St. and 23 Ave. in the ACTIVE testbed [8] was selected to evaluate the proposed method. Figure 6a demonstrates the geometric layout and the phase diagram of the target intersection.…”
Section: Evaluations and Analysismentioning
confidence: 99%
See 2 more Smart Citations